Bio Ecology and Germination Technology of Medicinal Chamomile (Сhamomilla Recutita L) - Isakov Tokhirjon; Qodirova Turdiniso; Jalolitdinov Muhiddin; Turg’unov Jaloliddin; Khusanov Bakhtiyor; Soliyev Sharobiddin (International Journal on Orange Technologies, 2021)
In the result of the necessity increase of medicinal plants, the amount of preparing their raw materials is raising too. This is resulting in the decrease of a number of medicinal plants in places where they grow; it may result in sharp limitation or complete decrease of the preparation of raw materials. Taking into consideration all these, germination of medicinal plants in conditions of irrigated typical brown soils and studying the influence of fertilizers on their raw materials and quality are considered as important problems of present time. For example, medicinal chamomile plant is one of the same plants. Over the past few years a number of scientists have been working on scientific investigations. As a result, leaves, stem, root and other parts of the plant were studied thoroughly and have been used in folk and modern medicine. А. Тurova, E. Sapojnikova made major investigations in 1982. Kh.Kh.Kholmatov, Due to the references given by А.I.Kosimov (1992-1999), А.Yo. Ibragimov (2005), А.Shomakhmudov (1993) Kh.Kh.Kholmatov, U. Yu. М. Мurdakhayev(1990-2001) and others, types of chamomile belong to Aasteraceae family and is considered to be a plant. MatricariaL flower of chamomile is used as a medical raw material. Its flower contains essential oil, carotene, vitamin C and other substances. In scientific medicine it is used as a means against inflammation, antiseptic, sedative, sweat and gas releasing. Hamazulene in the content of chamomile essential oil is widely used in medicine. Chamomile flower is used in chamomile tea and preparation of different herbs collection.